PERAN HUMAS PABRIK GULA (PG) SEMBORO JEMBER DALAM MENJAGA LOYALITAS KERJA KARYAWAN DAN CITRA PERUSAHAAN - Juariyah , Juariyah; Rahma, Alfina Maisya; Pratama, Aditya Dimas (Journal Social Politica, 2023)
In this study, with the title "The Role of Semboro Jember Sugar Factory Public Relations (PG) in Maintaining Employee Work Loyalty and Company Image," the aim is to determine the role of internal PG Semboro public relations in maintaining employee work loyalty and its obstacles, as well as the role of external PG Semboro public relations in maintaining the company's image and its obstacles. The theory used is the Cultip & Center theory. This type of research is included in qualitative descriptive research. Qualitative descriptive research is the activity of interpreting meaning, not using numbers, and managing interview results based on predetermined instruments using appropriate language and explanations according to the results of interviews with reality in the field. The results of this study are about describing the results of interview data on PG Semboro's public relations and public figures based on intellectual, religious, and government perspectives. This can be explained by PG Semboro's internal public relations strategy of maintaining employee loyalty by implementing employee relations programs with programs that will maintain employee loyalty. From this study, there are internal obstacles that hopefully, in the future, can be used as an evaluation to overcome these obstacles. In addition, there is an external public relations strategy that involves implementing programs with the community to maintain the company's image, and the obstacles to external public relations in maintaining the company's image can also be known.